DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR DETERMINATION OF SOME PESTICIDE RESIDUES IN WATER SAMPLES - Velkoska-Markovska, Lenche; Petanovska-Ilievska, Biljana (Macedonian Academy of Sciences and Arts, 2019)
The development of a new reversed-phase high-performance liquid chromatography method (RP-HPLC) with ultraviolet-diode array detection (UV-DAD) for simultaneous determination of 2,4-D, atrazine, malathion, fenitrothion and parathion residues in different water samples are described in this paper. The developed method has been validated according to European Commission guidelines for pesticide residue analytical methods, and all performance characteristics were found within acceptance criteria. The best separation and quantitative determination of the analytes were achieved using a LiChrospher 60 RP-select B (250 × 4 mm, 5 µm) analytical column, under the isocratic elution with mobile phase consisting of acetonitrile/water (60/40, V/V), flow rate of 1 ml/min, constant column temperature at 25 °C and UV-detection at 220 nm and 270 nm. The run time of analysis under the stipulated chromatographic conditions was about 10 min.
Keywords: RP-HPLC; UV-DAD; method validation; pesticide residues; water samples